Isolated metachronous splenic metastasis after rectal cancer surgery: a case report and literature review - Ren, Peide; Shi, Yihang; Zhang, Letian; Sun, Yuemin; Ye, Zhibin; Liu, Hengchang; Wang, Shunda; Chen, Yinggang (Frontiers in Oncology, 2025)
BackgroundThe occurrence of isolated splenic metastasis in association with colorectal cancer is exceedingly rare. This paper presents a case of isolated splenic metastasis identified one year after radical resection of rectal cancer. The patient underwent laparoscopic splenectomy, achieving favorable therapeutic outcomes. Furthermore, we conduct a literature review of analogous cases and examine the clinical diagnosis and therapeutic approaches for this uncommon condition.Case ReviewA 76-year-old male patient underwent laparoscopic radical resection for rectal cancer, accompanied by ileostomy, at our institution. Postoperatively, the patient received two cycles of XELOX chemotherapy but continued with oral capecitabine for six cycles due to oxaliplatin intolerance. Follow-up enhanced CT scans of the chest, abdomen, and pelvis revealed an isolated metastatic tumor in the spleen. Subsequently, the patient underwent laparoscopic splenectomy. Histopathological examination post-surgery confirmed the metastasis of rectal cancer to the spleen.ConclusionIsolated splenic metastasis originating from colorectal cancer is exceedingly rare, and laparoscopic splenectomy constitutes an effective treatment strategy.